Safety and Tolerability of Canagliflozin in Patients With Type 2 Diabetes Mellitus: Pooled Analysis of Phase 3 Study Results. Issue 3 (May 2014) - Usiskin, Keith; Kline, Irina; Fung, Albert; Mayer, Cristiana; Meininger, Gary
Abstract: Background: Canagliflozin is a sodium glucose cotransporter 2 inhibitor developed for treating type 2 diabetes mellitus (T2DM).Methods: The safety/tolerability profile of canagliflozin 100 and 300 mg over 26 weeks was assessed using an integrated analysis of data pooled from 4 placebo-controlled, phase 3 studies representing a broad range of patients with T2DM ( N = 2313; mean age, 56.0 years; glycated hemoglobin [HbA1c ], 8.0%; body mass index, 32.1 kg/m 2 ; estimated glomerular filtration rate, 88.1 mL/min/1.73 m 2 ) on various prespecified background diabetes mellitus treatments. Safety/tolerability evaluations included adverse event (AE) reporting, with additional data collection prespecified for selected AEs, and assessments of renal-related, lipid, and other safety laboratory parameters.Trial Registration: ClinicalTrials.gov, NCT01081834; NCT01106625; NCT01106677; NCT01106690.Results: The overall incidence of AEs was similar with canagliflozin 100 and 300 mg and placebo; incidences of serious AEs and AEs leading to study discontinuation were low across groups. Canagliflozin was associated with higher incidences than placebo of genital mycotic infections and osmotic diuresis–related AEs; these were generally considered by the investigator to be mild to moderate in intensity and infrequently led to discontinuation. Canagliflozin was associated with transient reductions in estimated glomerular filtration rate that trended toward baseline over the assessment period; incidences of renal-related AEs were low across groups. Dose-related increases in the incidence of hypoglycemia episodes were seen with canagliflozin versus placebo in patients on background sulfonylurea; incidences of severe hypoglycemia were low across groups. Hypoglycemia incidence was low overall in patients not on background sulfonylurea, but slightly higher with canagliflozin versus placebo. Relative to placebo, favorable changes in high-density lipoprotein cholesterol and triglycerides were seen with canagliflozin; increases in low-density lipoprotein cholesterol were also seen. Canagliflozin was associated with small changes in other safety laboratory parameters that were not clinically meaningful.Conclusions: Canagliflozin as monotherapy and as combination therapy was generally well tolerated in patients with T2DM inadequately controlled on their current diabetes mellitus treatment.